DIGITAL RISKS AND INFORMATION SECURITY OF THE CORPORATE SECTOR - SOROKIVSKA, Olena; KUZHDA, Tetiana; KINAL, Nazar (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores current issues of digital risks and information security in the corporate sector amid increasing cyber threats. The authors analyze the specifics of modern threats faced by companies, including risks of unauthorized access, data breaches, DDoS attacks, phishing campaigns, and malware. Special attention is given to the analysis of cybersecurity in wartime conditions, where companies become targets for hostile hacker groups aiming to destabilize the economy and undermine trust in businesses. The study presents the dynamics of the growing number of cyberattacks during 2022–2024, identifies the key business sectors most vulnerable to threats, and examines their impact on enterprises. A separate section is devoted to analyzing European experience in corporate cybersecurity, comparing the level of implementation of information security measures among EU and Ukrainian enterprises. The research has shown that despite the high level of awareness among Ukrainian companies regarding cybersecurity, the documentation of security policies and their regular review remain insufficient, increasing the likelihood of successful attacks. Based on the obtained results, a model for organizing and managing corporate information security has been developed. This model consists of five key components: organizational structure, technological solutions, risk management, corporate data protection, and control & audit. The proposed model aims to minimize cyber threats, enhance the resilience of the corporate environment, and strengthen trust among clients and partners. It can be utilized by company executives, IT specialists, and information security professionals to develop effective strategies for protecting corporate information systems in the context of digital transformation and increasing cyber threats.